KONVERSI TEPUNG SAGU MENJADI SIRUP GLUKOSA DENGAN MENGGUNAKAN KATALIS ASAM KLORIDAv - Edi Sutanto; Yusnimar Sahan; Deby Octavia (Universitas Riau, 2014)
Sago is one of carbohydrates potential resource for foods and raw materials in industries. Sago can beconverted to a glucose syrup by using HCl 0,5N as a catalyst. The purpose of this research is make glucosesyrup with the process of hydrolysis of sago flour and determining the influence of temperature, volume theaddition of acid and hydrolysis time on reducing sugar concentration of syrup produced. In order to get thehighest of glucose concentration in these syrup, in this research sago hydrolysis process have been doneunder variation of the volume acid (10, 15 and 20 ml), the hydrolysis temperatures (105, 115 and 125 o C) andthe hydrolysis time (15, 30 and 45 minutes). The glucose syrup were analyzed, such as water content by SNI08-7070-2005 and glucose content by the Nelson-Somogyi method. Based on the result, the highest ofglucose content in this syrup is 67.7% under condition the addition of 0.5 N HCl volume by 15 ml, hydrolysistime 30 minutes and temperature of 125 o C. The resulting glucose syrup meets the standard based on SNI 01-2978-1992 namely glucose concentration of more than 30% and a water content of less than 20%.Key words: glucose, glucose syrup, hydrolysis, HCl, sago starch